Metastatic INI-1−deficient undifferentiated lung cancer with EGFR 19del mutation identified in pleural effusion: a case report and review of the literature - Guo, Zhen; Li, Tianyuan; Duan, Xiufang (Frontiers in Oncology, 2025)
INI-1 is a core component of the switch/sucrose-non-fermenting (SWI/SNF) complex, an ATP-dependent chromatin remodeling complex that plays a critical role in DNA repair, transcriptional regulation, and cellular differentiation. Intrathoracic tumors driven by INI-1 inactivation are exceptionally rare. This report presents the first documented case of metastatic INI-1-deficient undifferentiated lung cancer harboring a co-occurring epidermal growth factor receptor (EGFR) exon 19 deletion mutation. The clinical and pathological characteristics of the tumor are described, followed by a comprehensive review of the relevant literature.